A hub covering flow network design resilient to major disruptions and supply/demand uncertainties. (2018) - Nasiri, Mohammad Mahdi; Shahmoradi-Moghadam, Hani; Torabi, Seyed Ali
This paper presents a robust methodology to deal with a novel resilient hub covering flow problem (HCFP) with capacity and budget constraints. The primary HCFP is to determine the best network setting, which minimises the total cost of establishing hubs and shipping the demand, subject to some constraints. In order to cope with the inherent uncertainty associated with the input data, a robust HCFP (RHCFP) is proposed. In order to evaluate the performance of the presented models, we use the Monte Carlo simulation technique to measure the efficiency of the robust model. In order to select the best conservatism level, we combine several measures for evaluating the value of a solution using a criterion called total performance measure (TPM), which demonstrates that the robust optimisation model performs better than the deterministic model in all cases.